A review of biomarkers for predicting clinical reactivity to foods with a focus on specific immunoglobulin E antibodies. Issue 3 (June 2015) - Sato, Sakura; Yanagida, Noriyuki; Ohtani, Kiyotaka; Koike, Yumi; Ebisawa, Motohiro
<x xml:space="preserve">Abstract</x> Purpose of review The purpose of this study is to assess the latest studies that focus on specific immunoglobulin (Ig)E antibodies for predicting clinical reactivity to foods. Recent findings Persistent hen's egg and cow's milk allergy patients have higher antigen-specific IgE levels at all ages than those who have outgrown these allergies. Recent studies on the natural histories of hen's egg and cow's milk allergies suggested that baseline antigen-specific IgEs are the most important predictors of tolerance. Oral immunotherapy (OIT), which is a novel therapeutic approach for food allergy, requires biomarkers for predicting outcomes after therapy. Several studies indicate that the initial antigen-specific IgE level may be a useful biomarker for the prognosis of OIT. Recently, component-resolved diagnostics (CRD) has been used for food allergy diagnosis. Current studies have suggested that Ara h 2, omega-5 gliadin and ovomucoid are good diagnostic markers for peanut, wheat and egg allergies, respectively. Summary Antigen-specific IgE can be a useful biomarker for predicting clinical reactivity to food allergies. Monitoring hen's egg and cow's milk-specific IgE is useful for predicting prognosis, and baseline specific IgE levels may be associated with the outcome of OIT. The use of CRD provides us with a better tool for diagnosing food allergy.